Action Strategies and Development Trends of Global Teacher Governance: An Analysis Based on Relevant Policies of International Organizations - YANG Pan; CHEN Shijian (Jiaoshi jiaoyu xuebao)
Global teacher governance is an important strategy to promote the development of the global knowledge economy. It aims to promote the construction of high-quality teachers through various governance means, and realize the comprehensive support for students' learning. In the 1960s, based on the concern of teacher status and teacher training, international organizations went through three stages of concern, exploration and promotion in the process of promoting global teacher governance, and showed a clear development trend. The main strategies of global teacher governance include reshaping teachers' professional status, standardizing teachers' educational responsibilities, leveraging teachers' professional wisdom, and focusing on teachers' professional growth. In the future, its development and promotion require strengthening external resolutions to guide the policy direction of teacher governance, increasing education assistance to improve the overall effectiveness of teacher governance, using policy borrowing to promote best practices in teacher governance, and conducting international evaluations to establish comparative mechanisms for teacher governance.